Ontogenetic colour change in Oreophryne ezra (Anura: Microhylidae) reflects an unusual shift from conspicuousness to crypsis but not in toxicity. (14th November 2017) - Bulbert, Matthew W; White, Thomas E; Saporito, Ralph A; Kraus, Fred
Abstract: Ontogenetic colour change (OCC) may signal a switch in defensive strategies across development. Commonly, juveniles use cryptic colours and transition to conspicuous coloration as adults. Extensive theoretical and empirical work suggest such a transition is more likely than the converse. Oreophryne ezra, a newly discovered frog from New Guinea, however, undergoes OCC that belies expectations. We investigated the notion juveniles are aposematic while the adults use crypsis. We quantified the extent of conspicuousness of O. ezra across life stages using spectrophotometry and models of avian vision; and analysed skin extracts for the presence of toxic alkaloids. As predicted, the juvenile colour patterns were estimated to be conspicuous to likely predators against the frogs natural viewing backgrounds, while adults consistently fell below the threshold of discriminability. However, we discovered no alkaloids in either juveniles or adults. This suggests the juveniles use alternative defensive chemicals, or the colour pattern has an alternative origin – to which we offer the hypothesis that juvenile frogs may be Batesian mimics of a synoptic species of weevil. This study highlights the potential for this system, and others like it, to inform our understanding of the adaptive significance of OCC and the selective drivers for different anti-predatory strategies.